PENINGKATAN PROMOSI DAN PENGARSIPAN DIGITAL SANGGAR SENI TARI DAN BUDAYA SAWO KECIK MELALUI PEMBUATAN WEBSITE AI - Nanang Sutisna; Suharyati, Henny; S. Putro, Sasongko; Yusar, Dedi; Seminingrat, Ratu Dini Andhiyani (LPPM Universitas Al Muslim, 2024)
ABSTRACT This community service activity aimed to develop and launch an artificial intelligence (AI)-based website as a promotional media and digital archive for the Cirebon Sawo Kecik Dance and Culture Art Studio. This is due to the need for this dance studio to increase its exposure in the digital world and archive works of art. In creating this website, a needs analysis was carried out, website development with AI integration, as well as training for studio members. From the results of implementing this activity, it was found that an interactive website can accommodate event promotion, adjust content to visitor preferences, and collect digital archive data of works of art. This community service activity also helped dance studios increasing their visibility online. Therefore, the application of AI technology in the form of a website has helped the Sawo Kecik Dance and Cultural Arts Studio achieve the studio's digital promotion and archiving goals well.